Evaluation of pre-donation anxiety and attitude of blood donors and its effect on blood pressure and pulse rate - Dr. Geet Bhuyan; Dr. Anjumoni Rabha; Dr. Rekha Tirkey; Dr. Sunil Ranga (Tropical Journal of Pathology and Microbiology, 2020)
Background: Previous negative experiences (NEs) during the process of blood donation can result in increased stress and is indicated by blood pressure and pulse rate, at a subsequent donation. The present study investigated the effect of attitude and anxiety in 1st time and regular blood donors with or without any previous NE on the pre-donation blood pressure and pulse rate. Materials and methods: Pre-donation blood pressure and pulse rate in 1st time and regular donors were measured. The attitude and anxiety were evaluated using a questionnaire and the relationship with a previous NE was assessed. Its effect on the blood pressure and pulse rate was subsequently evaluated. The study was a between-subjects, observational design. Results: Of the total 200 donors, 165 were males. 54 donors showed signs of anxiety whereas 33 donors had a previous NE. 11 donors (22.44%) who had a previous negative experience showed raised blood pressure whereas 9 donors (18.36%) with a previous negative experience showed a raised pulse rate. Both effective (-0.293) and cognitive (-0.0159) attitudes were negatively correlated with anxiety and were found to be statistically significant. Conclusion: No significant association was seen in a donor who experienced a negative experience in a previous visit with raised pre-donation blood pressure however, was significantly associated with a raised pulse rate. Moreover, anxiety and increased blood pressure, and increased pulse rate were assessed in first-time donors and it was seen that first-time donors especially showed raised blood pressure and pulse rate.